Integrating Health Into Disaster Risk Reduction Strategies: Key Considerations for Success - Dar, Osman; Buckley, Emmeline J.; Rokadiya, Sakib; Huda, Qudsia; Abrahams, Jonathan (American journal of public health (1971), 2014)
The human and financial costs of disasters are vast. In 2011, disasters were estimated to have cost $378 billion worldwide; disasters have affected 64% of the world’s population since 1992. Consequently, disaster risk reduction strategies have become increasingly prominent on national and international policy agendas. However, the function of health in disaster risk reduction strategies often has been restricted to emergency response. To mitigate the effect of disasters on social and health development goals (such as risk reduction Millennium Development Goals) and increase resilience among at-risk populations, disaster strategies should assign the health sector a more all-encompassing, proactive role. We discuss proposed methods and concepts for mainstreaming health in disaster risk reduction and consider barriers faced by the health sector in this field.